Effects of wheat gluten on nursery pig performance - B T Richert; J L Morrill; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1992)
One hundred eighty weanling pigs, averaging 23 d of age and 12.6 lb initial weight, were used to evaluate spray-dried wheat gluten (WG) in phase 1 (d 0 to 14) and(or) phase 2 (d 14 to 37) nursery diets. Phase 1 treatments were 1) dried skim milksoybean meal-dried whey-based control (DSM-SBM), 2) Diet 1 with WG and lactose used to replace the DSM (WG-SBM), and 3) Diet 1 with WG used to replace the SBM (DSM-WG). Phase 2 treatments were 1) corn-SBM-dried whey-based control and 2) WG and lactose used to replace the dried whey. During phase 1, diets with WG supported average daily gain (ADG), average daily feed intake (ADFI), and feedlgain (FIG) similar to the DSM-SBM control. Pigs fed the diet with DSM-WG had improved FIG compared to pigs fed WG-SBM. Diets with WG had increased DM and N digestibilities but caused increased serum urea N compared to the DSM-SBM control. In the first week of phase 2 (d 14 to 21), pigs previously fed WG-SBM and DSM-WG had improved FIG and DM and N digestibilities compared to those previously fed the DSM-SBM control. Pigs previously fed the WG-SBM treatment had improved ADG, ADFI, and FIG compared to pigs previously fed DSMWG. Overall (d 0 to 37), pigs fed WG in phase 1 had improved ADG and FIG compared to pigs fed the DSM-SBM control, and pigs fed WG-SBM during phase 1 had greater ADG and ADFI than pigs fed DSM-WG. As for the phase 2 diet treatments, dried whey supported improved ADG, ADFI, and FIG from d 14 to 21 compared to WG and lactose. However, for the entire phase 2 period (d 14 to 37) and overall (d 0 to 37), 41 pigs fed WG in phase 2 had similar ADG and improved FIG compared to those fed dried whey. In conclusion, pigs fed WG in place of DSM during phase 1 had improvements of 13% in ADG, 9% in ADFI, and 4% in FIG for the entire nursery period.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Dried skim milk; Wheat gluten; Nursery